Commission proposals on budgetary and financial reform - Gerhard Stahl (Intereconomics, 1987)
In a speech to the European Parliament on 18th February 1987 the Commission President Delors publicly announced the Commission's proposals for a fundamental reorganization of the system of financing the Community and of Community budgetary policy.1 What is the background of these proposals? How can they be assessed?
Keywords: 330; European Community